Utilization of YouTube as a Learning Media Algorithms of Programming for Students Informatics Engineering UNIPMA - Nita, Sekreningsih; Wicaksono, Dayu Agung (IC-ITECHS, 2024)
YouTube as an information sharing site is an application that is provided free of charge and is easy to access and use in various activities, on of which is for creating learning media. Learning with YouTube can improve skills and strengthen learning in the form of videos, making it easier to study and develop discussion material for Professional Educators. The purpose of using learning media via YouTube is to help Informatics students understand teaching material more easily and can motivate them to learn. The method in this research uses descriptive qualitative and collects primary and secondary data, namely students who take the 1st semester Algorithms of Programming course, class 1A, 1B, 1C totaling + 50 people and other internet users who watch videos on YouTube and library journals that are relevant to the research topic . The process and steps for making YouTube as a learning media include, 1) Making storyboards for material concepts 2) Making ppt files as discussion material 3) Making learning videos 4) Editing videos 3) Uploading videos to YouTube. The final result was +250 views, comments and likes. Whereas, learning videos can be viewed via the YouTube channel at the link https : // www.youtube.com / watch?v = bRsSFCc8kV0. The conclusion of this research is that using YouTube as a learning media makes learning more interesting, effective and very useful in the learning process and increases student motivation in learning more optimally because it can be played back to understand the material more deeply